The impact of the crisis on the Orthodox Church of Greece: a moment of challenge and opportunity?. Issue 1 (2nd January 2016) - Molokotos-Liederman, Lina
ABSTRACT: This article explores the impact of the economic crisis on the Orthodox Church of Greece (OCG). The first three parts of the article set the current stage by offering a short overview of the crisis and the response of the OCG through its charitable social welfare activities. The fourth part looks at church–state relations in Greece, covering more particularly its financial aspects. The fifth and final part discusses how the economic crisis has affected the OCG itself, including its own finances and governance, and sustainability and mission in the long term. Although the OCG provides social assistance to the Greek population during the economic crisis, it also finds itself very much affected by the same crisis. The economic crisis has forced the OCG to reduce its operating costs while at the same time continue its extensive social work. The crisis has also prompted public debates and questions about the finances of the OCG. This situation may gradually force either the Greek state or the OCG, or perhaps both, to rethink their relationship in the future.